2022
DOI: 10.3389/fmed.2022.877023
|View full text |Cite
|
Sign up to set email alerts
|

Update on overview of ocular manifestations of COVID-19

Abstract: The coronavirus disease 2019 (COVID-19) has become the most critical health crisis at present, and research is continued about the exact pathophysiology, presentations, and complications of this pandemic. It influences several organs, and many studies have addressed the organs, the involvement of which during the COVID-19 results in patients' death. One of the important organs that can be involved during COVID-19, which is also a transmission route of the disease, is the eye. According to the evidence, the sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 112 publications
0
15
0
Order By: Relevance
“…The long-term effects of COVID-19 on visual function and ocular anatomy are not yet fully understood. Some clinical studies have shown that SARS-CoV-2 can cause retinal vascular occlusions, including central retinal vein occlusion (CRVO), central retinal artery occlusion (CRAO), vitritis, and acute retinal necrosis (ARN) [ 46 ]. Because we observed the presence of S-antigen in various parts of the eye and SARS-CoV-2-induced cell death in cells lining the BRB, we aimed to evaluate the long-term consequences of S-antigen on overall retinal health.…”
Section: Resultsmentioning
confidence: 99%
“…The long-term effects of COVID-19 on visual function and ocular anatomy are not yet fully understood. Some clinical studies have shown that SARS-CoV-2 can cause retinal vascular occlusions, including central retinal vein occlusion (CRVO), central retinal artery occlusion (CRAO), vitritis, and acute retinal necrosis (ARN) [ 46 ]. Because we observed the presence of S-antigen in various parts of the eye and SARS-CoV-2-induced cell death in cells lining the BRB, we aimed to evaluate the long-term consequences of S-antigen on overall retinal health.…”
Section: Resultsmentioning
confidence: 99%
“…Viral transmission from eye tissue and its related secretions thus needs to be seriously considered, particularly regarding the direct proximity between persons or vector animals that could be encountered; this includes, for example, frontline workers, including medical personal or researchers, as well as vulnerable populations [ 82 , 83 ]. Mitigation approaches, in order to prevent direct ocular transmission could, therefore, include wearing eye shields or the application of a blocking agent, such as heparin-based formulations in the exposed face area [ 84 ]; these measures would be potent and personal protective approaches to limit the steady rise of viral transmission and ocular symptoms [ 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to preliminary clinical data, ophthalmologic COVID-19 cases can usually be characterised by an associated in ammatory state, vasculopathy, thrombotic microangiopathy, and intravascular coagulopathy [4].…”
Section: Sars-cov-2 Pathophysiological and Ophthalmological Correlatesmentioning
confidence: 99%
“…However, following or during infection, patients also demonstrated changes to their posterior eye segments, which are the subjects of these case studies. Further information about the connections of connections to retinovascular illnesses is continually being reported [2][3][4]. With a rise in newer and potentially more threatening variants of the COVID-19 virus, being acquainted with the possible clinical manifestations would pave the way for an effective treatment plan and improve patient clinical outcomes and visual acuity.…”
Section: Introductionmentioning
confidence: 99%